Simple and efficient solid phase extraction based on molecularly imprinted resorcinol–formaldehyde resin nanofibers for determination of trace sulfonamides in animal-origin foods. (15th March 2023) - Dai, Yuanyuan; Wu, Niu; Liu, Li-e; Yu, Fei; Wu, Yongjun; Jian, Ningge
Highlights: Molecular imprinted resin nanofibers (MIRF NFs) was prepared for the first time. MIRs material was first used in the form of NFs in SPE. High extraction efficiency for SAs was achieved by MIRF NFs. Simple and efficient detection method for multi-residue of SAs was developed. Abstract: Novel molecularly imprinted resorcinol–formaldehyde resin nanofibers (MIRF NFs) was prepared using polydopamine as an intermediate. With high specific surface area and favorable usability, MIRF NFs presented high efficiency for the solid phase extraction (SPE) of sulfonamides (SAs) in complex animal foods. After optimizing the operating conditions, a new method for SAs quantification coupled with HPLC–MS/MS was developed. By simple water dilution of the solvent extracts, SPE could be carried out. In addition, the eluent could be analyzed directly without any further treatment. The newly developed method was simplified greatly with much fewer sample pretreatment procedures (4 steps). Moreover, much fewer amounts of sample (1.0 g), adsorbent (3.0 mg), organic solvent (1.5 mL) and preparation time (20 min for 24 samples) were needed. The obtained good linearity (R 2  > 0.9957), low detection limits (0.01–0.14 μg kg −1 ), satisfactory recoveries (83.0 %–112.9 %) and precisions (RSDs < 12.6 %) further proved the feasibility of the method in practical application.